Comprehensive Approach to Adult Congenital Heart Disease - Sadeghpour, Anita.; Sadeghpour, Anita.; Kyavar, Majid.; Kyavar, Majid.; Alizadehasl, Azin.; Alizadehasl, Azin. (Springer London : Imprint: Springer, 2014)
This book presents unique cases of congenital heart disease (CHD) lesions, both corrected and non-corrected, and provides a thorough overview of the diagnostic tools available. It stresses the importance of taking an appropriate history and performing a suitable physical examination, and goes on to describe electrocardiography, chest X-ray, echocardiography, computed tomography, cardiovascular magnetic resonance imaging, and catheterization to ensure the reader has the best possible guidance in the diagnosis and management of adult CHD. Comprehensive Approach to Adult Congenital Heart Disease offers an extensive account of patients and their diagnostic and treatment modalities from first presentation to latest follow-up. Consequently, this invaluable resource provides a forum for all cardiologists, cardiology trainees and medical professionals seeking further opportunities to immerse themselves in the fascinating and ever-evolving field of adult CHD.